Pemberdayaan Ekonomi Masyarakat Melalui Dunia Digital di Era Covid-19 - Taufiqurrahman Taufiqurrahman; Abdul Azis; Ades Sugita (IAI Bunga Bangsa Cirebon, 2021)
Community empowerment in the midst of the Covid-19 pandemic, one of which is by introducing the use of digital marketing for MSME players. Digital marketing is a promotional activity and market search through online digital media by utilizing various means such as social networks and online product or service sales platforms. This research is a qualitative research with the aim of identifying the impact of digital marketing and the obstacles that occur in marketing products through digital marketing. The method of data collection is done by observation and interview techniques. The method of determining informants is carried out by snowball sampling to umkm entrepreneurs based on local food, handicraft, bumdes and maggot cultivation. The results show that MSME players are interested in using digital marketing and utilizing social media, but there are still some obstacles they experience such as low technology skills, they think that promoting products to digital marketing through social media and market places is something that is important. troublesome / complicated, the availability of internet access is limited, there are still many consumers who are worried about the security of transacting online.. Abstrak Pemberdayaan masyarakat di tengah pandemi covid-19 salah satunya dengan memperkenalkan pemanfaatan digital marketing bagi pelaku UMKM. Digital marketing adalah kegiatan promosi dan pencarian pasar melalui media digital secara online dengan memanfaatkan berbagai sarana misalnya jejaring sosial dan platform penjualan produk atau jasa online. Penelitian ini merupakan penelitian kualitatif dengan tujuan mengidentifikasi dampak digital marketing dan kendala yang terjadi dalam memasarkan produk melalui digital marketing. Metode pengambilan data dilakukan dengan teknik observasi dan wawancara. Adapun metode penentuan informan dilakukan secara snowball sampling kepada pengusaha umkm berbasis pangan lokal , handycraft, bumdes dan budidaya maggot. Hasil penelitian menunjukkan bahwa para pelaku UMKM tertarik untuk menggunakan digital marketing dan memanfaatkan media social, akan tetapi masih ada beberapa kendala yang mereka alami seperti kemampuan teknologi masih rendah, mereka menganggap bahwa untuk mempromosikan produk ke digital marketing melalui sosial media dan market place adalah hal yang menyusahkan/ribet, ketersediaan akses internet yang terbatas, masih banyak konsumen yang mengkhawatirkan keamanan bertransaksi secara online.